Comparison of WAB scores in Telugu monolinguals and Telugu-English bilingual speakers - K C, Shyamala; G, Swetha (Journal of All India Institute of Speech and Hearing, 2013)
Aphasia is a breakdown in the two-way translation processes that establishes the relation between thought and language. As a consequence, people with aphasia have an inability to translate, with reasonable fidelity. The Western Aphasia Battery (WAB, Kertesz, 1979 has become a popular protocol for the clinical evaluation of aphasia. The present study aimed to compare WAB scores across Normal Monolinguals (Telugu) and Bilingual (Telugu-English) Speakers across different age groups. The study was carried out among 120 typical adult Telugu speaking individuals in the age range of 20-70 years who were considered for control group. These 120 participants were categorized into five age groups like 20-30, 31-40, 41-50, 51-60 and 61-70 years with 24Participants in each group. Each group consists of 12 monolinguals (6males and 6 females) and 12 bilinguals (6 males and 6 females). All the Participants in the study have Telugu as their native language, and with no history of any neurological or psychiatric illness, alcoholism or drug abuse. All the participants were matched for their age, gender, language level, handedness, socio-economic status and educational level. Results revealed that bilingual participants performed better than monolingual participants in all the tasks in different age groups and also across both the genders. In the present study overall performance of bilingual participants was better than monolingual participants. Bilinguals are able to mastery over two different sets of skills or strategies than monolinguals and also all the bilingual participants in the study are from higher educational qualification and socio-economic status.